PERBEDAAN RESPONS TEKANAN DARAH TERHADAP COLD PRESSOR TEST BERDASARKAN INDEKS MASSA TUBUH DAN WAIST TO HEIGHT RATIO PADA MAHASISWA FK UPN "VETERAN" JAKARTA - Gabrielle Beatrix, (2023)
Obesity tends to be permanent and increases the risk of hypertension and cardiometabolic disease, therefore early screening is needed. This study was conducted to determine the differences in blood pressure responses during cold pressor test (CPT) for each body mass index (BMI) and waist-to-height ratio (WHtR) category on students at the Faculty of Medicine UPN "Veteran" Jakarta. The design of this study is cross-sectional with a simple random sampling technique on 76 students. The results showed that the majority of individuals with BMI < 23 had a normoreactive response (50%) and tend to have hyperreactive response (31%), while the majority of individuals with a BMI ≥ 23 had a hyporeactive response (41.2%) and tend to have normoreactive response (47.1%). The majority of individuals with risk WHtR had a hyporeactive response (40.5%) and tend to have normoactive response (45.2%), while the majority of individuals with non-risk WHtR had a normoactive response (52.9%) and tend to have hyperreactive response (32.4%). Chi-Square analysis shows that there is a significant difference in CPT blood pressure response based on BMI (p = 0.043) and WHtR (p = 0.026). The increase in BMI and WHtR corresponds to the decrease in CPT blood pressure response. This is related to increased activity of the RAAS and the decreased function of the sympathetic nerves.